Relationship Dissatisfaction, Emotion Regulation, and Physical Intimate Partner Aggression in Heavy-Drinking, Conflict-Prone Couples: A Dyadic Analysis - Halmos, Miklos B. (Journal of interpersonal violence, 2021)
Relationship dissatisfaction is a known risk factor for intimate partner aggression (IPA). However, the possible effect of weak emotion regulation skills on this association is unclear, particularly in couples at risk for violence who drink alcohol heavily. This study examined the moderating effect of emotion regulation on the association between relationship dissatisfaction and physical IPA perpetration within a dyadic framework. Participants were 583 heavy drinking couples (N = 1,166) with a recent history of psychological and/or physical IPA recruited from two metropolitan cities in the United States. Multilevel models were used to examine effects within an actor–partner interdependence framework. Gender, Actor dissatisfaction, and Actor and Partner emotion regulation were associated with greater physical IPA perpetration. Actor relationship dissatisfaction predicted significantly greater physical IPA perpetration in Actors characterized by weak versus strong emotion regulation. Furthermore, partner relationship dissatisfaction predicted significantly increased physical IPA perpetration in Actors reporting weak, versus strong, emotion regulation. Gender did not significantly interact with model variables. Utilizing the I3 metatheoretical model of IPA within a dyadic framework, results provide insight into the interactive effects of relationship dissatisfaction and emotion regulation deficits on physical IPA perpetration, particularly in those individuals already at risk for perpetration.